Why it's time to say goodbye to stavudine ... everywhere - Isabelle Andrieux-Meyer; Polly Clayden; Simon Collins; Nathan Geffen; Eric Goemaere; Mark Harrington; Sharonann Lynch; Tido von Schoen-Angerer; Tracy Swan (AOSIS, 2012)
The previous issue of the SAJHIV (December 2011) carried an Opinion piece by Innes, Cotton and Venter regarding the potential value of low-dose of stavudine (20 mg twice a day). They suggested that reduced dosing of stavudine may lead to levels of viral suppression comparable with those achieved with stavudine 30 mg bd but with a lower risk of toxicity and side-effects, and at a fraction of the cost of tenofovir. The Opinion was related to a larger proposal, led by Venter, to conduct a head-to-head trial comparing low-dose stavudine with tenofovir (both in a regimen including lamivudine and efavirenz) on viral suppression and other treatment outcomes over 24 months. There has been considerable debate regarding the advantages and disadvantages of low-dose stavudine, and in turn the value of any such trial. Here the debate continues with a commentary by Isabelle Andrieux-Meyer et al. and a rebuttal by Venter and colleagues.